Electrocatalytic activity, methanol tolerance and stability of perfluoroalkyl-substituted mononuclear, and ball-type dinuclear cobalt phthalocyanines for oxygen reduction in acidic medium - ÖZKAYA, ALİ RIZA; ÖZER, METİN (ROYAL SOC CHEMISTRY, 2009)
Electrocatalytic activitiy, methanol tolerance and stability of three phthalocyanine (Pc) complexes (a heptadecafluorononyl-substituted mononuclear CoPc 1, a pentaerythritol-bridged ball-type dinuclear Co2Pc2 2 and a heptadecafluorodecyl-substituted, pentaerythritol-bridged ball-type dinuclear Co2Pc2 3) and the performance of dual catalysts of 2/Pt and 3/Pt, dispersed on a high surface area carbon substrate, Vulcan XC-72 (VC) and Nafion (Nf), towards oxygen reduction (OR) were investigated and compared by surface cyclic voltammetry, rotating disk electrode, rotating ring-disk electrode and chronoamperometry experiments in acidic medium. The VC/Nf/3 modified glassy carbon electrode showed much higher catalytic performance, compared to VC/Nf/2 and VC/Nf/1 modified ones. The long term stability of the VC/Nf/3 catalyst in acidic medium was better than that of VC/Nf/2. It was found that the VC/Nf/1, VC/Nf/2 and VC/Nf/3 catalysts are nearly insensitive to the presence of methanol. In the presence of 1 M methanol in the electrolyte, the catalytic performances of 2- and 3-based catalysts were much better than that of the Pt-based one. Thus, it was shown that the VC/Nf/2-Pt and VC/Nf/3-Pt dual catalysts can be good alternatives to VC/Nf/Pt as cathode catalysts in direct methanol fuel cells. Moreover, in the absence of methanol, the mixing of 3 with Pt resulted in the enhancement of catalytic activity for OR, when compared to 3 and even Pt in the high overpotentials region.
Keywords: ELECTRICAL-PROPERTIES; HYDROGEN-PEROXIDE; ELECTROCHEMICAL REDUCTION; CATALYTIC-REDUCTION; SENSING PROPERTIES; MOLECULAR-OXYGEN; O-2 REDUCTION; ELECTROREDUCTION; CARBON; ELECTROLYTE